2018
DOI: 10.12659/pjr.902520
|View full text |Cite
|
Sign up to set email alerts
|

Structural Variations in Parotid Glands Induced by Radiation Therapy in Patients with Oral Carcinoma Observed on Contrast-Enhanced Computed Tomography

Abstract: SummaryBackgroundXerostomia is one of the commonest radiation-induced complications in patients with head and neck carcinoma. The aim of this study was to assess structural variations in parotid glands induced by radiation therapy in patients with oral carcinoma with contras-enhanced computed tomography (CECT).Material/MethodsA retrospective study was performed in 41 patients with oral carcinoma who underwent CECT for head and neck malignancies before and after radiotherapy. We analyzed the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 20 publications
3
6
1
Order By: Relevance
“…With regard to density changes, a significant variation was found in our study. In fact, increases of 30% on the right parotid gland and 24.9% on the left one (measured in HU) were observed, which corroborates the findings by Cheng et al [10], Ogura et al [11], and Wu et al [20]. However, Fiorino et al [22] and Xu et al [23] found reductions in the density of the glands.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…With regard to density changes, a significant variation was found in our study. In fact, increases of 30% on the right parotid gland and 24.9% on the left one (measured in HU) were observed, which corroborates the findings by Cheng et al [10], Ogura et al [11], and Wu et al [20]. However, Fiorino et al [22] and Xu et al [23] found reductions in the density of the glands.…”
Section: Discussionsupporting
confidence: 87%
“…is discrepancy can be explained by differences in the radiation dosage. Other studies [10,11] demonstrated that an increased density of salivary glands was observed with doses above 4.500 cGy, which was the case with all the patients in our study. Moreover, studies reporting a decrease in the density values point to a possible association with the gland's deformation [22].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Majority of the salivary secretion is contributed by the PGs. These are the largest salivary glands and are located at the pre-auricular region (1)(2)(3)(4)(5) . It is quite unfortunate that incidence of oral cancer is on rise.…”
Section: Introductionmentioning
confidence: 99%
“…However radiotherapy leads to various side effects, it is still considered as an important treatment modality for maxillofacial carcinoma patients (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) . Persistent xerostomia is one of the side effects due to radiation exposure and subsequent damage to parotid and submandibular salivary glands.…”
Section: Introductionmentioning
confidence: 99%